Prevalensi dan Profil Penderita Sindroma Koroner Akut dengan ST Segmen Elevasi (STEMI) di Rumah Sakit Umum Daerah dr. Fauziah Bireuen Tahun 2022-2023 - Aqilla Lutfiah; Aulia Mustika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Acute Coronary Syndrome (ACS) is an emergency condition in which a group of symptoms of acute ischemic chest pain are part of coronary heart disease (CHD) and require immediate treatment. The prevalence of CHD in Aceh is higher than the national average of 1.6% or around 20,244 people. This study is expected to describe the prevalence, number of deaths (mortality) and average length of stay (LOS) of STEMI patients during hospitalization so that this data can significantly enhance knowledge for health practitioners and be used as a warning to be more aware of STEMI incidents in Aceh. This study uses a retrospective descriptive research design with a research sample of all patients diagnosed with ACS with ST-Elevation who were hospitalized at Dr. Fauziah Hospital in June 2022-June 2023. The data collection technique is total sampling obtained from medical record data. It was concluded that the majority of patients were male, namely 80.7% (71 patients), the highest age was 45-60 years with 45 cases (51.1%). History of CHD was the dominant risk factor (62% of cases). The most dominant type of ACS with ST-Elevation was Anterior STEMI as many as 32 cases (52.3%) with onset <12 hours (51% of cases) and predominantly came with KILLIP I (62.5% of cases). The most dominant management was with conservative therapy 56 cases (61.4%). The average length of patient care was 5 days (45.1%) and the most outcomes with outpatients as many as 72 cases (81.8%).